Survey of Weight-loss Product Advertisements on the Internet - Rattanapongjinda, Netnapha; Plianbangchang, Pinyupa (Journal of Health Science of Thailand, 2017)
Nowadays, internet advertising is highly popular due to its effectiveness in reaching the target audience. In addition, its content can easily escape inspection by responsible authorities. The objective of this cross-sectional descriptive study was to survey information about weight-loss products advertised on the internet. The data were collected between November 2010 and January 2011. The sample was purposively selected from a population of websites as searched by Google Search Engine, resulting in 64 websites with information pertaining to 390 weight-loss products advertised in Thai language. The results indicated that there were 24 types of weight-loss products as categorized by the sellers. The three most frequently advertised were weight-loss food supplements (26.4%), weight-loss equipment (17.4%), and weight-loss or weight-control coffee (7.9%). About half (52.5%) of the sellers claimed that their products were guaranteed by the Thai Food and Drug Administration (FDA). Regarding its contents, the majority of advertisement (ads) showed instructions (76.9%). The other aspects shown were mechanisms of action (29.0%) and endorsement on product effectiveness (27.9%). Unfortunately, only 15.6 percent of the ads disclosed product cautions and contraindications, and only 3.6 percent exhibited product adverse reactions. In conclusion, weightloss products advertised on the internet were found to be of various types. The information presented violated law and regulations, especially the claim of Thai FDA endorsement. In addition, there were over-claims and omission of necessary information. For this reason, government authorities need to adjust their measures to appropriately control and alleviate this problem.